Conceptualizing emotions: a revised cognitive linguistic perspective - Kövecses, Zoltán (Poznań studies in contemporary linguistics, 2014)
Abstract Based on my earlier work on the conceptualization of emotions, I wish to emphasize a number of points in this paper. First, I suggest that emotion concepts are largely metaphorical and metonymic in nature. Second, I propose that several of the conceptual metaphors and metonymies are tightly connected. Third, in line with a large body of recent result, I maintain that many of our emotion concepts have a bodily basis, i.e. that they are embodied. Fourth, I concur with many others that our emotion concepts can be seen to have a frame-like structure, i.e. that they can be represented as cognitive-cultural models in the mind. Fifth, and on the methodology side, I claim that the description and analysis of emotion concepts requires both a qualitative and a quantitative methodology. Though most of these suggestions have been accepted and embraced by a number of scholars working on the emotions, several other scholars have challenged the suggestions. As a response to such challenges, I have revised and modified the ideas above in the past 25 years. The present paper is concerned with these more recent developments.